Os múltiplos usos do território, os impactos socioambientais e as relações conflitivas que permeiam a gestão ambiental na APA do Morro do Urubu em Aracaju, Sergipe, Brasil - Maria do Socorro Ferreira da Silva; Vicentina Anunciação; Hélio Mario de Araújo (Confins)
The Urban Conservation Units are threatened due to the effects of the urbanization process whose results imply forest fragmentation and loss of biodiversity. The research aims to analyze the socio-environmental impacts and challenges that compromise the management and conservation of the Morro do Urubu Environmental Protection Area in the city of Aracaju, Sergipe. While procedures were carried out: bibliographic and documental research; field research; and interview with the person responsible for managing the unit. The APA, located in the outskirts of the city near the Sergipe River, is the last forest remaining Atlantic Forest. This UC houses the City Park, the zoo, Mirante da Santa and the cable car used by residents and visitors for tourist, educational, leisure and recreation activities. However, despite the socio-environmental and tourist relevance, the problems resulting from urban pressure and real estate speculation, associated with low financial resources and reduced number of employees, make environmental management difficult and compromise the conservation of the APA. Thus, it is essential to seek participatory management strategies, based on critical Environmental Education, to bring the local population and other social actors together in favor of the conservation of the APA's natural resources.